Multiple dimensions of sleep are consistently associated with chronically elevated depressive symptoms from late pregnancy to 3 years postnatal in Indigenous and non-Indigenous New Zealand women. (July 2021) - Ladyman, Clare; Signal, T Leigh; Sweeney, Bronwyn; Jefferies, Mona; Gander, Philippa; Paine, Sarah-Jane; Huthwaite, Mark
Introduction: Poor sleep and depressive symptoms are common throughout the perinatal period, but little is known about the extended time course of depression and the sleep dimensions associated with these trajectories. Objective: This study investigated different depression trajectories in New Zealand Māori and non-Māori women from late pregnancy to 3 years postnatal. Relationships between multiple dimensions of sleep and these depression trajectories were also investigated. Methods: Data from 856 women (30.6% Māori and 69.4% non-Māori) from the longitudinal Moe Kura cohort study were used. Depressive symptoms and multiple dimensions of sleep (quality, duration, latency, continuity and daytime sleepiness) were collected at 36 weeks' gestation, 12 weeks postnatal and 3 years postnatal. Trajectory analysis was completed using latent class analysis. Results: Latent class analysis revealed two distinct groups of depressive symptom trajectories: 'chronic high' and 'stable mild' for both Māori and non-Māori women. Māori women in both trajectories were more likely than non-Māori women to have clinically significant depressive symptoms at every time point. Poorer sleep quality, latency, continuity and greater daytime sleepiness were consistently associated with the chronic high depressive symptom trajectory at all three time points, after controlling for sociodemographic factors. Conclusion: A significant proportion of Māori and non-Māori women experience chronically high depressive symptoms during the perinatal period and the following years. Across this extended time frame, Māori women have a higher probability of experiencing clinically significant depressive symptoms compared to non-Māori women. These persistent patterns of depressive symptoms occur concurrently with multiple dimensions of poor sleep. Given the well-described impact of maternal depression on the mother, child, family and community, this highlights the importance of healthcare professionals asking about mothers' sleep quality, continuity, latency and daytime sleepiness as potential indicators of long-term mood outcomes.